1998
DOI: 10.1039/a705634f
|View full text |Cite
|
Sign up to set email alerts
|

Arsenobetaine and other arsenic compounds in the National Research Council of Canada Certified Reference Materials DORM 1 and DORM 2

Abstract: A silica-based cation-exchange column was used to determine ence of arsenocholine in DORM 1 was questioned and suggested to be the tetramethylarsonium cation.6 the arsenic compounds in the National Research Council of Canada (NRCC ) CRMs DORM 1 and DORM 2 (Dogfish This paper reports the arsenic compounds identified in the dogfish reference materials DORM 1 and DORM 2 [separation Muscle). With a 20 mM aqueous pyridine mobile phase at pH 3.0, the concentration of arsenobetaine was only on anion-or cation-exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
43
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 9 publications
10
43
1
Order By: Relevance
“…4,7,8,11 The slightly lower concentration of AB found by extraction with water corresponds to the results of Londesborough et al 10 However, Mattusch and Wennrich reported an AB concentration of 16.5 mg As kg À1 dry mass obtained by extraction with water. 9 The presence of TMAO published by one working group as 0.4 mg As kg À1 dry mass 10 was not confirmed by our work, although this concentration is above the detection limit of our method.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…4,7,8,11 The slightly lower concentration of AB found by extraction with water corresponds to the results of Londesborough et al 10 However, Mattusch and Wennrich reported an AB concentration of 16.5 mg As kg À1 dry mass obtained by extraction with water. 9 The presence of TMAO published by one working group as 0.4 mg As kg À1 dry mass 10 was not confirmed by our work, although this concentration is above the detection limit of our method.…”
supporting
confidence: 79%
“…4 Many different extractants and extraction methods have been applied to this SRM. DORM-2, the successor to DORM-1, has recently been certified for arsenobetaine (AB; 16.4 AE 1.1 mg As kg…”
Section: Introductionmentioning
confidence: 99%
“…4B). This compound, also detected in extracts of the NRCC dogfish reference materials DORM1 and DORM2, 27,32 cannot be one of the dimethyl(ribosyl)arsine oxides that have been identified so far. 2 Under the chromatographic conditions used for the separation of the arsenic compounds in the liver extracts, dimethyl(ribosyl)-arsine oxides are clearly separated from this unknown compound (Figs 3A, 3B).…”
Section: Other Arsenic Compoundsmentioning
confidence: 77%
“…Plasma samples were extracted with a methanol:water mixture, 9:1 v/v (Goessler et al 1998a) followed by ion-exchange chromatography to separate quaternary arsonium compounds (AsB) from inorganic and anionic organic forms of arsenic (chemical symbol As) potentially present in samples and also to remove phosphate, which interferes with arsenic determination by GF-AAS (Welz & Sperling 1999). Exclusion of inorganic arsenic (H 3 AsO 4(aq) at equimolar concentration of AsB) and of phosphate (K 2 HPO 4(aq) , 800 ppm) was confirmed in preliminary experiments.…”
Section: Methodsmentioning
confidence: 99%